2012
DOI: 10.1039/c2cp40073a
|View full text |Cite
|
Sign up to set email alerts
|

Flavin as a photo-active acceptor for efficient energy and charge transfer in a model donor–acceptor system

Abstract: A donor-acceptor dyad model system using a flavin moiety as a photo-active acceptor has been synthesized for an energy and photo-induced electron transfer study. The photophysical investigations of the dyad revealed a multi-path energy and electron transfer process with a very high transfer efficiency. The photo-activity of flavin was believed to play an important role in the process, implying the potential application of flavin as a novel acceptor molecule for photovoltaics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, flavin's utility has already been appreciated based on empirical efforts, and elegant studies have employed flavins immobilized on electrodes or carbon nanotubes 85 as well as in a mobile phase of batteries. 86 Moreover, the electronic transitions we calculated are also being exploited in cases where flavins are in use as sensitizers for photochemical cells 85,87,88 or sensors. 89 While proteins tune flavin reactivity via multiple noncovalent interactions, we have demonstrated that even modification at a single position can change the way electron density is redistributed within the molecule as well as the associated energies.…”
Section: Concluding Remarks and Implications For Applicationsmentioning
confidence: 99%
“…However, flavin's utility has already been appreciated based on empirical efforts, and elegant studies have employed flavins immobilized on electrodes or carbon nanotubes 85 as well as in a mobile phase of batteries. 86 Moreover, the electronic transitions we calculated are also being exploited in cases where flavins are in use as sensitizers for photochemical cells 85,87,88 or sensors. 89 While proteins tune flavin reactivity via multiple noncovalent interactions, we have demonstrated that even modification at a single position can change the way electron density is redistributed within the molecule as well as the associated energies.…”
Section: Concluding Remarks and Implications For Applicationsmentioning
confidence: 99%
“…Broadband (425-715 nm) pump-probe femtosecond transient absorption spectra were recorded as described elsewhere. 22 The samples were placed in a quartz cuvette (Spectrocell FUV R-3002-T, 2 mm path length, internal dimensions 2 × 2 × 45 mm) and maintained at 25 °C using a temperature-controlled cuvette holder (QNW FLASH 300) under continuous stirring with an 8 mm diameter by 0.6 mm thick magnetic stirrer disc. Spectra were also collected from 340 to 600 nm at temperatures of 5 and 37 °C.…”
Section: Transient Absorption Spectroscopmentioning
confidence: 99%
“…The fluorescence emission studies clearly show that the flavin unit dominates the fluorescence properties of these systems, with substantial intramolecular quenching observed for the conjugated system 1 . The ability of 1 and 2 to accept multiple electrons coupled with their broad UV-Vis absorption properties make them promising acceptor molecules for organic photovoltaic systems; a direction we are currently exploring [21]. …”
Section: Discussionmentioning
confidence: 99%